The Influence of User Interface (UI), User Experience (UX), and E-Service Quality on Repurchase Intention with Customer Satisfaction as a Mediating Variable in Tokopedia E-commerce - Sri Purwantini, Hanif Naufal Rafii (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to examine the influence of User Interface (UI), User Experience (UX), and E-Service Quality on repurchase intention, with customer satisfaction serving as a mediating variable on the Tokopedia e-commerce platform. With the rapid growth of e-commerce in Indonesia, particularly on Tokopedia, factors such as UI and UX have become crucial in influencing customer satisfaction. This research adopts a quantitative approach, using a survey method to collect data from active Tokopedia users. The analysis investigates both the direct and indirect effects of UI, UX, and service quality on repurchase intention through customer satisfaction. The results indicate that good UI and UX, along with high-quality service, significantly enhance customer satisfaction, which in turn drives the intention to repurchase on Tokopedia. Keyword : User Interface, User Experience, E-Service Quality, Customer Satisfaction, Repurchase Intention, Tokopedia, E-Commerce